Efficient complement-mediated clearance of immunosuppressed T cells by macrophages - Gankema, Angela A. F.; Furumaya, Charita; Fernández-Hermira, Sara; Hoogenboezem, Mark; Matlung, Hanke L.; van Bruggen, Robin; Kuijpers, Taco W. (Frontiers in Immunology, 2023)
Cancer is one of the leading causes of death worldwide. Treatment outcome is largely dictated by the tumor type, disease stage, and treatment success rates, but also by the variation among patients in endogenous anti-tumor responses. Studies indicate that the presence of neutrophils in the tumor microenvironment is associated with a worse patient outcome due to their ability to suppress local anti-tumor T cell activity. Our previous studies investigated the mechanisms by which neutrophils suppress and damage T cells to become smaller in size (small T cells), debilitating their effector activities. Several studies indicate a role for tumor-associated macrophages in scavenging damaged or dead cells. We hypothesized that the observed lack of small T cells in the TME by confocal microscopy is due to immediate uptake by macrophages. In this study, we confirmed that indeed only the smaller, damaged T cells are taken up by macrophages, once serum-opsonized. Damaged T cells opsonized with complement factor C3 fragments were phagocytosed by macrophages, resulting in almost instantaneous and highly efficient uptake of these small T cells. Inhibition of the complement receptors CR1, CR3 and CR4 expressed by macrophages completely blocked phagocytosis. By contrast, actively proliferating T cells (large T cells) were neither impaired in neutrophil-MDSC activity nor opsonized for phagocytosis by macrophages. Rapid removal of damaged T cells suggests a role of complement and macrophages within the tumor microenvironment to clear suppressed T cells in cancer patients.